A REVIEW ON MULTIPURPOSE MEDICINAL PROPERTIES OF TRADITIONALLY USED PSIDIUM GUAJAVA LEAVES - AHAMAD, ADIL; ANSARI, S H (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Psidium guajava is an important food crop and medicinal plant available in tropical and subtropical countries. P. guajava (Guava), belonging to the family of Myrtaceae. P. guajava Linn. (Guava) is used not only as food but also as folk medicine in subtropical areas around the world because of its pharmacologic activities. It contains important phytoconstituents such as tannins, triterpenes, flavonoid, quercetin, pentacyclic triterpenoid, guajanoic acid, saponins, carotenoids, lectins, leucocyanidin, ellagic acid, amritoside, beta-sitosterol, uvaol, oleanolic acid, and ursolic acid. Conventionally, guava is used for the treatment of various ailments such as antioxidant, hepatoprotective, anti-allergy, antimicrobial, antigenotoxic, antiplasmodial, cytotoxic, antispasmodic, cardioactive, anti-cough, antidiabetic, anti-inflammatory, and antinociceptive activities, supporting its traditional uses.